Perioperative use of transthoracic echocardiography in a patient with congenitally corrected transposition of great arteries, atrial septal defect and severe pulmonary stenosis for lower segment cesarean section - Vikas Saini; Tanvir Samra; Gurpreet Kaur (Wolters Kluwer Medknow Publications, 2017)
A 25-year-old female with congenitally corrected transposition of great arteries (CCTGAs), atrial septal defect, and severe pulmonary stenosis underwent lower segment cesarean section at 34 weeks of gestation using combined spinal epidural anesthesia (CSEA). We used transthoracic echocardiography (TTE) for intraoperative monitoring of the cardiovascular system because these patients are reported to have a high prevalence of myocardial perfusion defects, regional wall motion abnormalities, and impaired ventricular contractility. Scanning was done at four different time intervals; preoperatively, after initiation of CSEA, after delivery of child and postoperatively (6 and 24 h postdelivery) to detect regional wall motion and valvular abnormalities, calculate ejection fractions and optimize fluid administration. In this case report, we thus discuss the anatomical defects of CCTGA, physiologic concerns and emphasize on the use of TTE for perioperative management of such cases.